PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) MATEMATIS BERBASIS PBL TERINTEGRASI NILAI-NILAI ISLAM DI SEKOLAH DASAR ISLAM TERPADU - MZ, Zubaidah Amir; Anggraini, Fitria; Kusnadi, Kusnadi; Alfiah, Alfiah (PD PGMI se Indonesia, 2019)
This research is a development research using a 4-D model, but in this study, researchers modified it to 3-D (Define, Design, Development). This study aims to produce PBL-based Student Worksheet (DMSW) Integrated Islamic Values that are valid, practical, and effective. This research was conducted at SDIT Raudhaturrahmah sub-district Marpoyan Damai, Pekanbaru, Riau. The subject of this study were material experts and media from lecturers and teachers, as well as Raudhaturrahmah Pekanbaru students. The sample in this study was class V Al-Halim as the experimental class and class V Al-Fattah as the control class. The object of this research is PBL Mathematical DMSW Integrated Islamic Values. The type of data used is in the form of quantitative and qualitative data. The instruments of data collection were questionnaires, interviews and posttest. The data analysis technique used is quantitative descriptive analysis and qualitative descriptive analysis. Based on the validity test, the DMSW based on PBL-Based Islamic Values was stated as a very valid category with a percentage of validity level of 87.61%, and very practical with a percentage of practicality of 84.39%. And effective, because based on the results of t test analysis, there are differences in learning outcomes between experiments using problem-based mathematics DMSW integrated Islamic values with the control class that does not use problem-based DMSW integrated Islamic values. besides, the percentage of student learning completeness reaches 85%.